SOSIALISASI UPAYA BELA NEGARA MELALUI PENERAPAN PROTOKOL KESEHATAN COVID-19 PADA SANTRIWAN DAN SANTRIWATI TPA MASJID BAITUL JAMAAH BATU KUWUR DESA SUKARARA - Uwi Martayadi; Dyah Indraswati (Sekolah Tinggi Pariwisata Mataram, 2021)
The emergence of Coronavirus Disease 2019 (Covid-19) has caused countries around the world including Indonesia to experience problems in various aspects of life because the virus can attack anyone of any age (elderly, adult, children, infants, or pregnant women). The presence of this virus creates a new habit that gives rise to the term new normal with health protocols (wearing masks, keeping distance, and washing hands with soap in running water). Many people, santriwan and santriwati children have not implemented health protocols. The purpose of the service is to provide an understanding of the importance of applying Covid-19 health protocols to santriwan and santriwati TPA Baitul Jamaah Batu Kuwur Mosque to prevent transmission to others. The stage in this devotion began from communication conducted with ustadz who taught at the TPA Masjid Baitul Jamaah Batu Kuwur, asking permission to conduct observation and socialization. The next stage is observation, identifying problems by observing during landfill activities. The last stage is socialization, providing an understanding of the importance of state defense efforts through the application of health protocols. The results of the service showed that santriwan and santriwati did not implement health protocols during landfill activities because of their incomprehension about Covid-19. The socialization made Santriwan and santriwati's understanding increase in the implementation of Covid-19 health protocols.